Absence of hereditary p53 mutations in 10 familial leukemia pedigrees. - Felix, C A (1992)
Germline p53 mutations have been identified in the Li-Fraumeni syndrome but the role of such mutations in familial leukemia is not established. The p53 gene was examined by single-strand conformation polymorphism analysis of exons 4-8 in 10 families with multiple members affected with leukemia. The diagnoses included acute and chronic leukemias and Hodgkin's disease. Identified in two families were p53 mutations that were nonhereditary. These included a 2-bp deletion in exon 6 found in the lymphoblast DNA of one child whose sibling, cousin, and several adult relatives had acute leukemia. The other nonhereditary p53 mutation was a transition at codon 248 (CGG to CAG, arginine to glutamine) found in the lymphoblasts of a patient with a preleukemic syndrome and acute lymphoblastic leukemia (ALL) whose brother is a long-term survivor of ALL. Thus, p53 mutations were found to occur in two families but both were nonhereditary. Moreover, in the remaining eight families no p53 mutation was identified in the regions of p53 where most mutations have been found in other cancers. Although p53 mutations sometimes may be present, they do not appear to be a primary event responsible for hereditary susceptibility to familial leukemia. This study suggests involvement of other genes or mechanisms.